Teneligliptin, a DPP-4 Inhibitor, Improves Vascular Endothelial Function via Divergent Actions Including Changes in Circulating Endothelial Progenitor Cells - Akashi N; Umemoto T; Yamada H; Fujiwara T; Yamamoto K; Taniguchi Y; Sakakura K; Wada H; Momomura SI; Fujita H (Diabetes, Metabolic Syndrome and Obesity, 2023)
Naoyuki Akashi,1 Tomio Umemoto,1 Hodaka Yamada,2 Takayuki Fujiwara,3 Kei Yamamoto,1 Yousuke Taniguchi,1 Kenichi Sakakura,1 Hiroshi Wada,1 Shin-ichi Momomura,1 Hideo Fujita1 1Division of Cardiovascular Medicine, Jichi Medical University Saitama Medical Center, Saitama, Japan; 2Division of Endocrinology and Metabolism, Jichi Medical University Saitama Medical Center, Saitama, Japan; 3Department of Cardiovascular Medicine, The University of Tokyo Hospital, Tokyo, JapanCorrespondence: Tomio Umemoto, Division of Cardiovascular Medicine, Jichi Medical University Saitama Medical Center, 1-847 Amanuma-cho, Omiya-ku, Saitama, 330-8503, Japan, Tel +81-48-647-2111, Fax +81-48-648-5188, Email to-ume@omiya.jichi.ac.jpPurpose: Dipeptidyl peptidase-4 (DPP-4) inhibitors increase endothelial progenitor cells (EPCs) in peripheral blood circulation. However, the underlying mechanisms and effects on vascular endothelial function remain unclear. We evaluated whether the DPP-4 inhibitor teneligliptin increases circulating EPCs by inhibiting stromal-derived factor-1α (SDF-1α) and improves flow-mediated vascular dilatation (FMD) in type 2 diabetes mellitus patients with acute coronary syndrome (ACS) or its risk factors.Patients and Methods: This single-center, open-label, prospective, randomized controlled trial evaluated 17 patients (hemoglobin A1c ≤ 7.5% and peak creatinine phosphokinase < 2000 IU/mL) with ACS or a history of ACS or multiple cardiovascular risk factors. Metabolic variables of glucose and lipids, circulating EPCs, plasma DPP-4 activity, and SDF-1α levels, and FMD were evaluated at baseline and 28 ± 4 weeks after enrollment. Patients were randomly assigned to either the teneligliptin (n = 8) or control (n = 9) groups.Results: The DPP-4 activity (∆− 509.5 ± 105.7 vs ∆32.8 ± 53.4 μU/mL) and SDF-1α levels (∆− 695.6 ± 443.2 vs ∆11.1 ± 193.7 pg/mL) were significantly decreased after 28 weeks in the teneligliptin group than those in the control group. The number of EPCs showed an increasing trend in the teneligliptin treated group; albeit this did not reach statistical significance. Glucose and lipid levels were not significantly different between the groups before and after 28 weeks. However, FMD was significantly improved in the teneligliptin group when compared to the control group (∆3.8% ± 2.1% vs ∆− 0.3% ± 2.9%, P=0.006).Conclusion: Teneligliptin improved FMD through a mechanism other than increasing the number of circulating EPCs.Keywords: endothelial progenitor cell, teneligliptin, DPP-4 inhibitor, flow-mediated dilation, type 2 diabetes mellitus